EFFECT FORTIFICATION OF Chlorella sp. POWDER TO NATA DE SEAWEED QUALITY - Antonius Sihombing; Syahrul '; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The aim of the research was to determine the effect of fortification Chlorella sp. which can be used as a substitute for urea in the manufacture of nata de seaweed and the quality of nata de seaweed produced from fortified Chlorella sp powder. The method used was this research is experimental method that is making nata de seaweed which fortified with Chlorella sp. different amount . The design used was non-factorial complete randomized design (CRD) which consisted of 4 levels, namely NR0 (urea 5g), NR1 (2g Chlorella), NR2 (4g Chlorella) and NR3 (6g Chlorella). The parameters used were sensory evaluation and procsimate evaluation. Based on the results of this study it can be concluded that use of Chlorella sp. can be used as a substitute for urea in the manufacture of nata which has been prohibited its use. The best treatment of the four treatments used was by using Chlorella sp. as much as 6g, with average organoleptic value (color 3,76, odour 3,66, texture 4,10 and taste 3,93), water content 87,75%, ash 0,21%, protein content 1,56 %, And 0.34% crude fiber content.Keywords: Seaweed, Nata, Chlorella, Urea